2015
DOI: 10.1098/rspb.2014.2778
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for three-dimensional elaboration of theAquilegiapetal spur

Abstract: By enforcing specific pollinator interactions, Aquilegia petal nectar spurs maintain reproductive isolation between species. Spur development is the result of three-dimensional elaboration from a comparatively two-dimensional primordium. Initiated by localized, oriented cell divisions surrounding the incipient nectary, this process creates a pouch that is extended by anisotropic cell elongation. We hypothesized that the development of this evolutionary novelty could be promoted by non-mutually exclusive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(133 citation statements)
references
References 51 publications
12
120
1
Order By: Relevance
“…All the TRV2 constructs contained a fragment of the gene ANTHOCYANIN SYNTHASE ( AqANS ) as a silencing marker. Because AqSTY1 exhibited the strongest differential expression between the petal blade and spur (Yant et al ., ), we first silenced the expression of AqSTY1 alone in 349 A. coerulea individuals. Although 105 plants showed silencing of the AqANS marker and were confirmed to have specific downregulation of AqSTY1 , no obvious morphological phenotype was recovered (Figs 3e, S4a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the TRV2 constructs contained a fragment of the gene ANTHOCYANIN SYNTHASE ( AqANS ) as a silencing marker. Because AqSTY1 exhibited the strongest differential expression between the petal blade and spur (Yant et al ., ), we first silenced the expression of AqSTY1 alone in 349 A. coerulea individuals. Although 105 plants showed silencing of the AqANS marker and were confirmed to have specific downregulation of AqSTY1 , no obvious morphological phenotype was recovered (Figs 3e, S4a).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, studies in many different angiosperm systems have suggested that auxin is more likely to play a role in nectar production and secretion rather than in determining the identity of the nectaries themselves. Perhaps most significantly, our previous RNAseq results found that while STY homologs all show strong spur cup‐specific enrichment, no homologs of YUC , or any other known STY1 target (Ståldal et al ., ), were recovered as cup‐enriched (Yant et al ., ). This suggests that the otherwise conserved STY /auxin regulatory pathway may not apply to the nectary, but it still remains possible that some other component of canonical STY1 function, perhaps related to cell type differentiation, has a parallel in nectary development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is congruent with a model in which KNOX activity has been co-opted to promote and maintain further morphogenetic potential during late stages of petal development. Interestingly, recent transcriptome analysis of the developing Aquilegia spur failed to identify upregulation of KNOX genes, suggesting that this clearly convergent trait develops through different genetic programs in different species (Yant et al 2015). Further research will determine the ontogenetic mechanisms and genetic machinery that have been recurrently recruited to generate nectar spurs and modulate their length in distant angiosperm lineages.…”
Section: International Journal Of Plant Sciencesmentioning
confidence: 97%
“…In Linaria, much of the petal spur length was attained by cell expansion while the initial outgrowth may incorporate a short period of cell division, generating much of the length of the corolla tube and petal spur (Box et al, 2011). Given that organ sculpting via localized cell division is the key factor determining the initiation of nectar spurs in Aquilegia (Yant et al, 2015), with cell elongation rather than cell division responsible for variation in length of the spurs once the spur is formed (Puzey et al, 2012), development of the corolla in both shape and size may involve multiple processes. In Petunia, differences in tube length of mature flowers are controlled by a combination of cell length and cell number, with cell number being the most important contributor.…”
Section: Discussionmentioning
confidence: 99%